HUMAN RESOURCE MANAGEMENT AND LABOR LAW PROTECTION IN INTERNSHIP PROGRAMS ADDRESSING EXPLOITATION LEARNING QUALITY AND CORPORATE COMPLIANCE - Firdausi Nuzula Rahmadani; Tegar Raffi Putra Jumantoro (Penelitian dan Pengembangan Ilmu, 2025)
Internships are vital for youth transitions into work but often lack legal protection and coherent Human Resource Management (HRM) design. This study examines Indonesia’s apprenticeship law and HRM frameworks to assess alignment and propose reforms. The objectives are to map statutory rules, identify enforcement gaps, and recommend HRM-informed policies. The method is normative juridical using library research of primary legal sources, ministerial regulations, and doctrinal literature. Analysis follows a deductive doctrinal method, extracting legal norms and synthesizing them with HRM concepts on program design, supervision, compensation, assessment, and governance. Implementation focused on close reading of Law Number 13 of 2003 on Employment and Minister of Manpower Regulation Number 6 of 2020. Findings indicate that the legal framework mandates written apprenticeship agreements, supervisory provisions, allowances, safety coverage, and certification, yet enforcement is inconsistent. Gaps include variable allowance practices, weak monitoring, and limited sanctions that permit exploitative placements. Conceptual HRM analysis suggests that clear competency outcomes, trained mentors, transparent compensation, and governance reduce exploitation and improve employability. The study concludes that strengthening legal standards must be paired with regulator-backed HRM guidance and employer incentives. Recommendations prioritize enforcement enhancement, minimum allowance benchmarks, mentor capacity building, and co-designed assessment rubrics with education partners.